Determinants of Muzakki Decisions in Choosing Zakat Payment Through Formal Institutions - Mojang Zulfa Amadea; Aas Nurasyiah; Ripan Hermawan Sastra; Rifka Aulia (Center of Strategic Studies (PUSKAS) BAZNAS, 2025)
The significant gap between the potential zakat collection of Rp327.6 trillion and the actual realization of Rp22.4 trillion challenges zakat management in Indonesia. Rp61.258 trillion in zakat funds remain unrecorded in the National Zakat Report (LZN) due to informal payments through mosques, Islamic boarding schools, or directly to recipients, leading to potential dishonesty and inequality. This study aims to identify the factors influencing the decision to pay zakat through official Zakat Management Organizations (OPZ) in Indonesia, comparing urban and rural muzakki. The research employs Structural Equation Modelling - Multigroup Analysis (SEM-MGA) using SmartPLS for data analysis. The subjects are 400 muzakki in Indonesia who have paid zakat through OPZ. The research findings indicate that trust and accessibility significantly and positively impact the decision to pay zakat through OPZ for both urban and rural muzakki. However, zakat knowledge and income do not influence rural muzakki decisions but have a positive effect on urban muzakki. The regional classification moderates the impact of accessibility on the decision to pay zakat through OPZ but does not moderate the influence of trust, zakat knowledge, and income. This research provides a comparative analysis of urban and rural muzakki, offering new insights into regional differences in zakat payment behavior. The findings of this study also provide practical implications for zakat institutions and policymakers in aligning zakat programs with the Sustainable Development Goals (SDGs).